Factors that motivate Latvian consumers to purchase products and services from social enterprises in Latvia: the case of socially responsible consumption - Casno, Kristīne; Šķiltere, Daina; Sloka, Biruta (My University, 2019)
The purpose of the study is to -determine the relative importance of various factors that motivate Latvian consumers to purchase products and services from social enterprises in order to provide practical suggestions and recommendations for Latvian social enterprises that would allow them to improve their performance. The primary method used by the study is quantitative research by the means of an online survey of Latvian consumers of social enterprise products /services. The results of the research indicate that Latvian consumers find the product / service quality aspects, as well as aspects of social responsibility and convenience of the shopping location, on average, as most motivating to purchase products / services of social enterprises. However, the results of factor analysis highlight the importance of emotional aspects during on-site shopping as well as the importance of digital presence. Focus on the aforementioned could lead to optimal performance of social enterprises with limited marketing budgets. Authors also found that such factors as pleasant atmosphere and friendly service have the highest potential to generate repeat purchases among Latvian consumers, as confirmed by a statistically significant correlational relationship between the aforementioned factors and actual purchasing behavior of Latvian social enterprise consumers. Online sales also have potential to increase the economic performance of Latvian social enterprises. Consumers who regard online shopping highly on average display a less active shopping behavior which could be improved by offering online shopping opportunities. Authors also found that, while communication of social value is still recommended as vital part of social enterprise marketing, it should not be the only focus of social enterprise marketing activities and associated communication.
Keywords: consumer value research; social entrepreneurship; marketing; social enterprise; marketing research; Research Subject Categories::SOCIAL SCIENCES::Business and economics